Features of the Security System Development of a Computer Telecommunication Network - Swarna Surekha, (The Bioscan, 2024)
Global computer networks have enabled ordinary users, companies, organizations and medical institutions to gain virtually unlimited access to data arrays. Therefore, developing systems capable of ensuring the good performance and secure operation of a standard Computer Telecommunication Network (CTN) has become one of the most pressing tasks demanded in the medical industry. Consequently, this study aims to create an ordered chain of operations that can perform information encryption to enhance data transmission and exchange security. This study examines the existing ordered chains of encryption operations and assesses their strengths and weaknesses. In addition, a framework for implementing cryptographic algorithms is proposed. This algorithm structure enables verification of the existence of the correct key along the specified path, thereby enhancing the overall security of the system. The study results indicate that the optimal variant of encryption is the ordered chains of encoding operations that rely on cryptography. The results of the testing demonstrated that the developed ordered chain of operations exhibited several advantages compared to its analogs, with an efficiency that exceeded that of the analogs by more than fourfold. The implementation of the proposed ordered chain of operations would provide a significantly safer operation of a standard CTN in a typical Medical Institution (MI).